2011
DOI: 10.3109/09273948.2011.569110
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Low- and High-dose Glucocorticoids on the Innate Immunity of Corneal Epithelium in Vitro

Abstract: Low-concentration hydrocortisone enhances the expression and function of TLRs in HCEC and provides evidence for a novel function of glucocorticoids in innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The local immunosuppression caused by topical glucocorticoids could be the result of an inhibition of innate defense mechanisms of epithelial cells and/or functions of professional immune cells. In support of these hypotheses, studies in humans and mice demonstrated that topical glucocorticoids are able to downregulate the expression of Toll‐like receptor 2 and Toll‐like receptor 4 by corneal epithelial cells and fibroblasts, reduce expression of antimicrobial peptides and reduce recruitment and activation of immune cells involved in innate and adaptive immunity …”
Section: Discussionmentioning
confidence: 94%
“…The local immunosuppression caused by topical glucocorticoids could be the result of an inhibition of innate defense mechanisms of epithelial cells and/or functions of professional immune cells. In support of these hypotheses, studies in humans and mice demonstrated that topical glucocorticoids are able to downregulate the expression of Toll‐like receptor 2 and Toll‐like receptor 4 by corneal epithelial cells and fibroblasts, reduce expression of antimicrobial peptides and reduce recruitment and activation of immune cells involved in innate and adaptive immunity …”
Section: Discussionmentioning
confidence: 94%
“…Glucocorticoid effects on human corneal epithelial cells have been previously reported for a few target genes (16,20,21), however, the genome wide actions of glucocorticoids have not been established. To address this issue, we performed western blotting in immortalized human corneal epithelial cell line to first determine if glucocorticoid receptor is expressed (18).…”
Section: Resultsmentioning
confidence: 99%
“…Opacification of the lens or cataract formation are also adverse events seen in sustained corticosteroid use. Glucocorticoids have also been reported to be synthesized in the human ocular surface and they have the ability to regulate corneal immune response (5-7). In the cornea, glucocorticoids have been shown to regulate their circadian rhythm (8,9), inhibit blood and lymphatic vessel growth (10,11), curb inflammation (12-15), and increase epithelial integrity under a hypoxic challenge (16), as well as retard wound healing in rabbits (17).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, low concentration of DEX induced a 3-fold increase in IL-1β production in unstimulated blood, whereas high concentration of DEX suppressed the production of this cytokine. Enhancement of innate immune responses by low concentrations of glucocorticoids, including TLR2 and -4 expression and IL-6, CXCL8 and IL-1 production, through upregulation of DUSP1 and de-phosphorylation of MAPK p38, have previously been reported [ 52 53 ].…”
Section: Discussionmentioning
confidence: 99%